2010
DOI: 10.1111/j.1742-4658.2010.07554.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental consequences of alternative Bcl‐x splicing during preimplantation embryo development

Abstract: Elevated cell death in human preimplantation embryos is one of the cellular events compromising pregnancy rates after assisted reproductive technology treatments. We therefore explored the molecular pathways regulating cell death at the blastocyst stage in human embryos cultured in vitro. Owing to limited availability of human embryos, these pathways were further characterized in mouse blastocysts. Gene expression studies revealed a positive correlation between the cell death index and the expression of Bcl‐x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
(74 reference statements)
0
11
1
Order By: Relevance
“…Accordingly, several studies have shown an important role of BCL2-L1 in the regulation of embryonic cell death in pig [18,34,35,41], mouse [42], human [43], and cattle [44][45][46]. In contrast, some studies have shown that the levels of BCL2-L1 transcripts did not correlated with blastocyst quality [47,48].…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, several studies have shown an important role of BCL2-L1 in the regulation of embryonic cell death in pig [18,34,35,41], mouse [42], human [43], and cattle [44][45][46]. In contrast, some studies have shown that the levels of BCL2-L1 transcripts did not correlated with blastocyst quality [47,48].…”
Section: Discussionmentioning
confidence: 86%
“…The standard concentration of the generated pTOPO-Mito was quantitated using nanodrop and utilized in qPCR. Mitochondrial DNA copy number in single oocytes was determined as previously described [36].…”
Section: Mitochondrial Dna Copy Number Using Quantitative Pcrmentioning
confidence: 99%
“…The transcription of the BAX homolog BAK and the BH3-only member HRK appears to be up-regulated in fragmenting embryos at the four-cell stage (Jurisicova et al 2003, Metcalfe et al 2004, suggesting a potential role for these proapoptotic members in regulating embryonic death and fragmentation in a redundant manner to BAX or upstream of BAX, respectively. Furthermore, an alternative splicing of the BCL2L1 gene in favor of the short proapoptotic isoform BCL2L1S was observed in a subset of human and mouse fragmented and/or dying embryos (Jurisicova et al 1998, Perumalsamy et al 2010, suggesting that subtle post-transcriptional modifications could be implemented to regulate embryonic fate. Accordingly, decreasing the BCL2L1L/BCL2L1S ratio in mouse embryos by using an antisense strategy that up-regulates BCL2L1S and concomitantly downregulates BCL2L1L has severely affected embryonic developmental competence (Perumalsamy et al 2010).…”
Section: Role Of Bcl2 Family Members In Preimplantation Embryo Demisementioning
confidence: 99%
“…Furthermore, an alternative splicing of the BCL2L1 gene in favor of the short proapoptotic isoform BCL2L1S was observed in a subset of human and mouse fragmented and/or dying embryos (Jurisicova et al 1998, Perumalsamy et al 2010, suggesting that subtle post-transcriptional modifications could be implemented to regulate embryonic fate. Accordingly, decreasing the BCL2L1L/BCL2L1S ratio in mouse embryos by using an antisense strategy that up-regulates BCL2L1S and concomitantly downregulates BCL2L1L has severely affected embryonic developmental competence (Perumalsamy et al 2010). …”
Section: Role Of Bcl2 Family Members In Preimplantation Embryo Demisementioning
confidence: 99%